THE USABILITY OF THE I-SYAIR APPLICATION IN LEARNING ARABIC POETRY AMONG UNIVERSITY STUDENTS - Che Amran, Aisyah Aminah; Osman, Rahmah Ahmad H.; Alosman, Abdulrahman; Ahmad Johor, Muhammad Ajwad Mohamad; Yushasnul, Muhammad Nora’ziim; Idris, Isyah Radhiah; Kasim, Rohayati; Khairallah, Christian (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study aims to evaluate the usability of the i-Syair application in learning Arabic poetry among university students. The i-Syair integrates Augmented Reality (AR) and interactive multimedia to create an engaging and immersive learning experience, bridging classical Arabic literature with modern technology. Guided by the Tawhidic paradigm of balanced human development encompassing intellect (‘aql), spirit (rūh), and body (jasad), the study assesses three key aspects of usability: usefulness, satisfaction, and ease of use. Employing a quantitative descriptive design, data were collected from 33 respondents enrolled in the Bachelor of Arabic Language and Literature program through a structured questionnaire using a five-point Likert scale. The results, analyzed using IBM SPSS version 26, revealed that i-Syair achieved a high mean score across all dimensions, indicating strong user acceptance and positive learning impact. Students reported that the AR features significantly enhanced their comprehension and enjoyment of Arabic poetry, transforming learning into an interactive experience rather than mere memorization. The findings affirm that i-Syair is a user-friendly and pedagogically effective tool that supports modern Arabic learning while embodying technological innovation and Islamic educational values.